Insights and Recommendations for Research Integrity Construction in Light of Retraction Issues - Yan QIN; Jing XU (Yixue yu zhexue)
This study focuses on the analysis of the academic characteristics of the retracted literature of SCI journals in stomatology, aiming to identify the root causes of academic misconduct and propose improvement strategies. Relevant data were collected from retraction databases, and the characteristics and reasons for retraction were statistically analyzed. The results show that 112 papers were retracted from 91 journals, with primary document retraction events accounting for 84.82%. Papers in interdisciplinary fields had a higher retraction rate. Spain, China, and the United States collectively accounted for nearly half of the retractions, with 87.5% being co-authored papers. Data falsification (41.07%) and issues with results (16.81%) are the main reasons. Over the past decade, the time lag for retraction has been significantly shortened (P＜0.05). Research suggests that scientific research institutions and publishers improve the review mechanism, implement peer review reforms such as involving "international reviewers", build a platform for academic misconduct monitoring and scientific research integrity supervision, thereby promoting a higher level of research integrity.